Pengaruh Green Brand Image dan Green Brand Trust terhadap Keputusan Pembelian AMDK Merek AQUA di Kota Medan - Sabrina Romaito Hutagalung; Parenta Ritonga; Nasrudin Nasrudin; Jamardua Haro; Jenny Sari Tarigan (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The phenomenon of extreme warming has increased public concern for the environment, one of which is reflected in environmentally friendly purchasing behavior. Many companies, including the AMDK brand Aqua, compete to create environmentally friendly products. Aqua's eco-friendly branding attracts attention, especially in the midst of environmental issues. Green brand image and green brand trust are factors that influence consumer purchasing decisions. This study aims to examine the effect of green brand image and green brand trust on purchasing decisions for the Aqua brand bottled water in Medan City. This research uses quantitative research methods with descriptive types. The data analysis technique used is multiple regression analysis using the SPSS version 26 program, involving 90 respondents. Data collection techniques were carried out through questionnaires and literature studies. The results showed that green brand image and green brand trust have a positive and significant effect on purchasing decisions for the Aqua brand bottled water in Medan City, both partially and simultaneously. The results of the study based on the coefficient of determination test show that green brand image and green brand trust are able to explain 48% of the influence of purchasing decisions, while the remaining 52% is explained by other variables not examined in this study.